Quantitative assessment of SARS‐CoV‐2 RNAemia and outcome in patients with coronavirus disease 2019. Issue 5 (1st March 2021) - Tang, Kefu; Wu, Lei; Luo, Ying; Gong, Bo
Abstract: The disease spectrum of coronavirus disease 2019 (COVID‐19) varies from asymptomatic infection to critical illness and death. Identification of prognostic markers is vital for predicting progression and clinical practice. Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) RNA, known as RNAemia, has been detected in the blood. However, the potential clinical value of SARS‐CoV‐2 RNAemia remains unknown. We, therefore, conducted a meta‐analysis using a random‐effects model to estimate the pooled prevalence of SARS‐CoV‐2 RNAemia as well as summary strength of RNAemia in association with disease severity and unfavorable clinical outcomes. A total of 21 studies involving 2181 patients were included. SARS‐CoV‐2 RNAemia in COVID‐19 patients varied from 9.4% to 74.1%, with a pooled estimate of 34% (95% confidene interval [CI]: 26%–43%). Overall, SARS‐CoV‐2 RNAemia was associated with COVID‐19 severity with odds ratio (OR) of 5.43 (95% CI: 3.46–8.53). In addition, SARS‐CoV‐2 RNAemia was a significant risk factor for unfavorable clinical outcomes (OR = 6.54, 95% CI: 3.82–11.21). The summary OR was 4.28 (95% CI: 2.20–8.33) for intensive care unit (ICU) admission, 11.07 (95% CI: 5.60–21.88) for mortality. Furthermore, RNAemia was also a significant risk factor for invasive mechanical ventilation and multiple organ failure. SARS‐CoV‐2 RNAemia is associated with disease severity, ICU admission, death in COVID‐19, and may serve as a clinical predictor. More prospective trials in evaluating the potential of SARS‐CoV‐2 RNAemia as a prognostic indicator are necessary.